Introduction and evaluation of a 'pre-ART care' service in Swaziland: an operational research study. Issue 2 (15th March 2012) - Burtle, David; Welfare, William; Elden, Susan; Mamvura, Canaan; Vandelanotte, Joris; Petherick, Emily; Walley, John; Wright, John
Abstract : Objective: To implement and evaluate a formal pre-antiretroviral therapy (ART) care service at a district hospital in Swaziland. Design: Operational research. Setting: District hospital in Southern Africa. Participants: 1171 patients with a previous diagnosis of HIV. A baseline patient group consisted of the first 200 patients using the service. Two follow-up groups were defined: group 1 was all patients recruited from April to June 2009 and group 2 was 200 patients recruited in February 2010. Intervention: Introduction of pre-ART care—a package of interventions, including counselling; regular review; clinical staging; timely initiation of ART; social and psychological support; and prevention and management of opportunistic infections, such as tuberculosis. Primary and secondary outcome measures: Proportion of patients assessed for ART eligibility, proportion of eligible patients who were started on ART and proportion receiving defined evidence-based interventions (including prophylactic co-trimoxazole and tuberculosis screening). Results: Following the implementation of the pre-ART service, the proportion of patients receiving defined interventions increased; the proportion of patient being assessed for ART eligibility significantly increased (baseline: 59%, group 1: 64%, group 2: 76%; p=0.001); the proportion of ART-eligible patients starting treatment increased (baseline: 53%, group 1: 81%, group: 2, 81%; p<0.001) and the median time between patients being declared eligible for ART and initiation of treatment significantly decreased (baseline: 61 days, group 1: 39 days, group 2: 14 days; p<0.001). Conclusions: This intervention was part of a shift in the model of care from a fragmented acute care model to a more comprehensive service. The introduction of structured pre-ART was associated with significant improvements in the assessment, management and timeliness of initiation of treatment for patients with HIV.